Concurrent nonvolatile resistance and capacitance switching in LaAlO3 - Wu, Shuxiang (2011)
We report on the correlated nonvolatile resistance and capacitance switching in Pt/LaAlO3/Nb:SrTiO3 heterostructures. The pristine devices show the typical characteristics of a Schottky junction; however, after forming, a reverse bias switches the device into a low resistance and high capacitance state while a forward bias drives it into a high resistance and low capacitance state. Our experiments suggest that both the formation of conducting filaments and the modulation of interface barrier contribute to the resistance switching. Oxygen vacancies play critical roles in determining the switching characteristics and can be controlled in the process of device fabrication.